Therapeutic Effect of Repurposed Temsirolimus in Lung Adenocarcinoma Model - Chang, Hsuen-Wen; Wu, Min-Ju; Lin, Zih-Miao; Wang, Chueh-Yi; Cheng, Shu-Yun; Lin, Yen-Kuang; Chow, Yen-Hung; Ch’ang, Hui-Ju; Chang, Vincent H. S. (Frontiers in Pharmacology, 2018)
Lung cancer is the leading cause of cancer-related deaths worldwide among men and women. The poor prognosis and resistance to both radiation and chemotherapy urged the development of potential targets for lung cancer treatment. In this study, using a network-based cellular signature bioinformatics approach, we repurposed a clinically approved mTOR inhibitor for renal cell carcinomas, temsirolimus, as the potential therapeutic candidate for lung adenocarcinoma. The PI3K-AKT-mTOR pathway is known as one of the most frequently dysregulated pathways in cancers, including non-small cell lung cancer (NSCLC). By using a well-documented lung adenocarcinoma mouse model of human pathophysiology, we examined the effect of temsirolimus on the growth of lung adenocarcinoma in vitro and in vivo. In addition, temsirolimus combined with reduced doses of cisplatin and gemcitabine significantly inhibited the lung tumor growth in the lung adenocarcinoma mouse model compared with the temsirolimus alone or the conventional cisplatin–gemcitabine combination. Functional imaging techniques and microscopic analyses were used to reveal the response mechanisms. Extensive immunohistochemical analyses were used to demonstrate the apparent effects of combined treatments on tumor architecture, vasculature, apoptosis, and the mTOR-pathway. The present findings urge the further exploration of temsirolimus in combination with chemotherapy for treating lung adenocarcinoma.